Cover Feature: The Tris(pentafluoroethyl)stannate(II) Anion, [Sn(C2F5)3]−—Synthesis and Reactivity (Chem. Eur. J. 58/2017). Issue 58 (18th August 2017) - Wiesemann, Markus; Klösener, Johannes; Niemann, Mark; Neumann, Beate; Stammler, Hans‐Georg; Hoge, Berthold
Abstract : The acidic tris(pentafluoroethyl)stannane sweetens the chemistry of tin. The reaction with the reversed polar tri‐ n ‐butyltin hydride afforded the highly polarized unsymmetrical distannane. In the reaction with bases, the three electron‐withdrawing pentafluoroethyl substituents stabilize the readily transferable tris(pentafluoroethyl)stannate(II) anion, a compound which should not be missed in the cocktail of basic organotin chemistry. More information can be found in the Full Paper by B. Hoge et al. onpage 14476 .